The Effect of Service Quality and Relationship Quality on Satisfaction and Its Impact on Consumer Loyalty Towards the Distribution of Reefer Container Meat by PT Indogal Trading - Rizky Reynaldi; Wilhelmus Hary Susilo; April Gunawan Malau; Imam Fahcruddin (Dinasti Review, 2024)
This study aims to examine the influence of service quality and relational quality on customer satisfaction and its impact on customer loyalty in the distribution of refrigerated (reefer) containerized meat by PT Indogal Trading. The primary issue identified is the low levels of customer satisfaction and loyalty, which are affected by service issues such as delivery delays, temperature fluctuations, and suboptimal complaint management. The study population consists of 105 PT Indogal Trading customers in 2023, representing 50 companies, with a sample of 83 respondents selected using simple random sampling. Data were collected through a questionnaire and analyzed using SMART PLS. The findings indicate that service quality and relational quality have a significant effect on both customer satisfaction and loyalty. Furthermore, customer satisfaction mediates the influence of service quality and relational quality on customer loyalty. In conclusion, improving service quality and relational quality can significantly enhance customer satisfaction and loyalty. Managerial recommendations include increasing service consistency, improving temperature management, and enhancing responsiveness to customer complaints to strengthen customer loyalty.